If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3560 + 15x = c Solving 3560 + 15x = c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3560' to each side of the equation. 3560 + -3560 + 15x = -3560 + c Combine like terms: 3560 + -3560 = 0 0 + 15x = -3560 + c 15x = -3560 + c Divide each side by '15'. x = -237.3333333 + 0.06666666667c Simplifying x = -237.3333333 + 0.06666666667c
| (n-4)(n-7)=0 | | 7x-2/-4=-10 | | Y-2.4=9 | | 4x^3-280x^2+4900=4x^3-200x^2+2500x | | 6m-(9+2m)= | | 8x+(5x+12)=90 | | 6(x-7.6)=8.4 | | 4x^3-200x^2+2500x=4x^3-280x+4900x | | r^2=-28 | | -21x=-108 | | 7x+6.73=4x+10 | | V/11=4/5 | | 113=6x-5(2x-13) | | 4x^3-280x+4900x=4x^3-200x+2500x | | (3x+60)=180 | | 2(3y-1)-x=0 | | 7.2a+5.54=-15.34 | | 2(3x+2)+2(4x-5)=22 | | 7.6x=-62.32 | | 6-y+1+4y=43 | | X-6=2.64 | | 32x+23=x-8 | | x^2+4x+5=26 | | -9(3b+2)+(28b-3)=0 | | 2y^3-3y^2-12y+2x^2-6x+5=0 | | x^2+2x+8y-47=0 | | -2y=1.98 | | 5x-(4x-5)=0 | | (x+4)(x-8)=28 | | x^2+4+5=26 | | X+2.2=6.8 | | 66+6x=-77-7x |